2020
DOI: 10.1007/s11842-020-09460-7
|View full text |Cite
|
Sign up to set email alerts
|

Parcelized Cut-and-Carry Agroforestry Systems for Confined Livestock

Abstract: We characterize a parcelized land management system that does not meet traditional co-located agroforestry practices in the tropics. A cut-and-carry agroforestry system for confined livestock emphasizes land utilization as a source of fodder, cutting and carrying feed from parcels to paddocks near a farmer’s home. It reduces feed cost by utilizing parcels under private, shared, and/or public ownership. Within cut-and-carry systems, we distinguish between those where parcels are managed as monocrops and traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, rigorous land management must continue to be practiced to keep the visual soil structure quality score from deteriorating (Rathore et al 2020;Tormena et al 2016). Land degradation will occur if the monoculture system with conventional agriculture continues (Seruni et al 2021). Planting trees as a source of organic matter to reduce soil density is the major technique to enhance soil structure quality (Siqueira et al 2020).…”
Section: Visual Soil Structure Qualitymentioning
confidence: 99%
“…Furthermore, rigorous land management must continue to be practiced to keep the visual soil structure quality score from deteriorating (Rathore et al 2020;Tormena et al 2016). Land degradation will occur if the monoculture system with conventional agriculture continues (Seruni et al 2021). Planting trees as a source of organic matter to reduce soil density is the major technique to enhance soil structure quality (Siqueira et al 2020).…”
Section: Visual Soil Structure Qualitymentioning
confidence: 99%
“…The intensification in agriculture planting patterns has occurred because of the increased land use in agriculture [26,27]. Intercropping in teak private forests plays a role in providing short-term (food), medium (livestock) and long-term (wood) needs for smallholders [26,27]. Teak has been the dominant tree in Gunungkidul private forests [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several programs to increase farmers' knowledge of forest management, for instance, the establishment of Sekolah Lapangan (Field School) for farmers under the supervision of the Department of Forestry (Yumi et al, 2015) and the Master Treegrower Traning Program (Anggraini et al, 2021). Previous studies confirmed that the farmers' adoption of innovative approaches is low; hence it poses a challenge to modern forest management (Anggraini et al, 2021;Seruni et al, 2021). Rather than acquiring innovation, farmers who hold extensive lands are more likely to manage their timbers (Sabastian et al, 2014(Sabastian et al, , 2019.…”
Section: The Dynamics Of Livelihoods Vegetation Coverage and Politica...mentioning
confidence: 98%
“…Although there is a wealth of literature discussing the success of agroforestry, the dynamis of livelihoods due to political interventions in this karst landscape have not been widely covered. There have been several studies about teak agroforestry (Maharani et al, 2022;Roshetko et al, 2013;Udayana et al, 2020) and livelihoods (Seruni et al, 2021), but the political aspects are still missing, although several studies indicate that the successfulness of the agroforestry program in Gunungkidul was widely linked with political movements initiated by the governments. (Awang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%